2020
DOI: 10.21203/rs.3.rs-137388/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Waist-to-Height Ratio, Waist Circumference, Body Mass Index and Risk of Cardiometabolic Multimorbidity: A National Longitudinal Cohort Study

Abstract: Background: Cardiometabolic multimorbidity is an increasing public health burden. This study aimed to evaluate the association of waist-to-height ratio (WHtR), waist circumference (WC) and body mass index (BMI) with risk of cardiometabolic multimorbidity.Methods: We used data from the China Health and Retirement Longitudinal Study (CHARLS). 10521 participants aged 45 and over were recruited, including 8807 individuals with 0 cardiometabolic disease at baseline (stage Ⅰ) and 1714 individuals with 1 cardiometabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
(53 reference statements)
0
1
0
Order By: Relevance
“…The association between adiposity and multimorbidity has been extensively explored in epidemiological studies [12,23,24,[36][37][38]. For instance, a systematic review and meta-analysis of 8 longitudinal studies found a higher risk of multimorbidity among individuals with obesity [36].…”
Section: Discussionmentioning
confidence: 99%
“…The association between adiposity and multimorbidity has been extensively explored in epidemiological studies [12,23,24,[36][37][38]. For instance, a systematic review and meta-analysis of 8 longitudinal studies found a higher risk of multimorbidity among individuals with obesity [36].…”
Section: Discussionmentioning
confidence: 99%